2016
DOI: 10.7567/jjap.55.06je03
|View full text |Cite
|
Sign up to set email alerts
|

Study on the contact resistance of various metals (Au, Ti, and Sb) on Bi–Te and Sb–Te thermoelectric films

Abstract: In this study, we explore various electrode materials (Au, Ti, and Sb) for use as contact materials on Bi2Te3 and Sb2Te3 thermoelectric films. Using the transmission line method (TLM), we measured the specific resistivity of the contacts, which showed that Au has the lowest contact resistivity for both the thermoelectric films (after annealing): 2.7 × 10−10 Ω m2 for Bi2Te3 and 2.9 × 10−11 Ω m2 for Sb2Te3. The specific contact resistivity data suggest that the dominant factor for the contact properties is inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The SEM images of the Bi 2 Te 3 –Cu multilayer films are shown in Figure . The interfaces are tough in all our samples due to the different oriented microstructures of our Bi 2 Te 3 films (e.g., R a ), which indicates the possibility of the influence of surface states on the contact resistance . Additionally, it can be observed that many defects such as pores generate at the interface between the two layers of Sample 1 (Figure a–c), which may block the transport of electrons and thus result in a large contact resistance.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The SEM images of the Bi 2 Te 3 –Cu multilayer films are shown in Figure . The interfaces are tough in all our samples due to the different oriented microstructures of our Bi 2 Te 3 films (e.g., R a ), which indicates the possibility of the influence of surface states on the contact resistance . Additionally, it can be observed that many defects such as pores generate at the interface between the two layers of Sample 1 (Figure a–c), which may block the transport of electrons and thus result in a large contact resistance.…”
Section: Resultsmentioning
confidence: 91%
“…Figure is the total resistance plotted as a function of pad spacing for contacts between different oriented Bi 2 Te 3 and Cu measured by TLM, where the contact area is designed as 0.12 mm 2 (<0.4 mm 2 ). The well-fitted lines show the reliability of the TLM model . Extracted R c and ρ c are listed in the table below Figure .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, as the field of thin-film electronics moves towards flexible applications, the use of ITO is limited as it fails quickly under strain 61,63 . The choice of electrode material, therefore, is highly dependent on the specific application, with TCOs (still predominantly ITO) continuing in established FPD manufacturing, while new alternatives such as carbon nanotubes, graphene, and metallic grids stand to replace ITO when optical transparency is still required but cost and/or flexibility become concerns 41,61,[64][65][66][67] , while simple metal films (or bi-and tri-layer stacks of metals) can be used where transparency is unnecessary and material and processing costs are dominant [68][69][70] , discussed further in section 3.2.4.…”
Section: Transparent Metal Oxides As Transparent Electrodesmentioning
confidence: 99%
“…Yb0.3Co4Sb12 [14] Mo-Ti 9 Bi2Te3 [27] Au 2.73 Mg2Si [28] Ni 210 Hf0.5Zr0.5CoSn0.2Sb0.8 [29] Ag 38 (Mm,Sm)yCo4Sb12 [26] Fe-Ni 2 n-type skutterudite [30] CoSi2 0.4 This work…”
Section: Thermoelectric Materials Metallization Layer Specific Contacmentioning
confidence: 99%